Incomes in Göteborg 1925 - Gustafsson, Björn; Johansson, Mats (University of Gothenburg, 2011)
The aim of this study is to throw light on why inequality in the distribution of income in Sweden fell from the mid-1920s to the second part of the 1950s. For this reason the project decided to collect income information referring to different years from a sample of households for one Swedish city. A database was created by coding tax records and other documents for the city of Göteborg, the second largest city in Sweden.

The determination of which years to investigate was critical. For analysing changes over time it was thought as essential to have roughly equal numbers of years between years studied. Further, it was thought advisable to avoid years with too much macroeconomic turmoil as well as the years of the two World Wars. Balancing the resources for the data collection between the size of a sub sample and the number of subsamples, it was decided to assemble data for four years. The years 1925, 1936, 1947 and 1958 was chosen to investigate. It should be pointed out that the year 1947 was preferred to the following years as large social insurance reforms leading to increases in pension benefits and the introduction of child allowances were put in effect in 1948.

Household is defined from registers kept in the archives (Mantalslängder). A household is defined as persons with the same surname living in the same apartment or single-family house. This means that there can be people belonging to more than two generations in the same household; siblings living together can make up a household as well. Foster children are included as long as they are registred at the same address. Adult children are considered to be living in the household of their parents as long as they are registred at the same address. In almost all cases, servants and tenants not belonging to the household are treated as separate households.

Purpose:

The aim of this study is to throw light on why inequality in the distribution of income in Sweden fell from the mid-1920s to the second part of the 1950s

The aim of this study is to throw light on why inequality in the distribution of income in Sweden fell from the mid-1920s to the second part of the 1950s. For this reason the project decided to collect income information referring to different years from a sample of households for one Swedish city. A database was created by coding tax records and other documents for the city of Göteborg, the second largest city in Sweden.

The determination of which years to investigate was critical. For analysing changes over time it was thought as essential to have roughly equal numbers of years between years studied. Further, it was thought advisable to avoid years with too much macroeconomic turmoil as well as the years of the two World Wars. Balancing the resources for the data collection between the size of a sub sample and the number of subsamples, it was decided to assemble data for four years. The years 1925, 1936, 1947 and 1958 was chosen to investigate. It should be pointed out that the year 1947 was preferred to the following years as large social insurance reforms leading to increases in pension benefits and the introduction of child allowances were put in effect in 1948.

Household is defined from registers kept in the archives (Mantalslängder). A household is defined as persons with the same surname living in the same apartment or single-family house. This means that there can be people belonging to more than two generations in the same household; siblings living together can make up a household as well. Foster children are included as long as they are registred at the same address. Adult children are considered to be living in the household of their parents as long as they are registred at the same address. In almost all cases, servants and tenants not belonging to the household are treated as separate households.

Syfte:

Syftet med studien var att belysa varför ojämlikhet i inkomst minskade från mitten på 1920-talet till andra hälften av 1950-talet.
Inkomster i Göteborg 1925
Keywords: Income, property and investment/saving; Inkomster, egendom och investeringar/sparande; HISTORY; HISTORIA; Social Sciences; Samhällsvetenskap; Economic History; Ekonomisk historia